Enhanced Antitumor Efficacy by 808 nm Laser‐Induced Synergistic Photothermal and Photodynamic Therapy Based on a Indocyanine‐Green‐Attached W18O49 Nanostructure. (6th November 2015) - Deng, Kerong; Hou, Zhiyao; Deng, Xiaoran; Yang, Piaoping; Li, Chunxia; Lin, Jun
Abstract : A novel nanoplatform based on tungsten oxide (W18 O49, WO) and indocyanine green (ICG) for dual‐modal photothermal therapy (PTT) and photodynamic therapy (PDT) has been successfully constructed. In this design, the hierarchical unique nanorod‐bundled W18 O49 nanostructures play roles in being not only as an efficient photothermal agent for PTT but also as a potential nanovehicle for ICG molecules via electrostatic adsorption after modified with trimethylammonium groups on their surface. It is found that the ability of ICG to produce cytotoxic reactive oxygen species for PDT is well maintained after being attached on the WO, thus the as‐obtained WO@ICG can achieve a synergistic effect of combined PTT and PDT under single 808 nm near‐infrared (NIR) laser excitation. Notably, compared with PTT or PDT alone, the enhanced HeLa cells lethality of the 808 nm laser triggered dual‐modal therapy is observed. The in vivo animal experiments have shown that WO@ICG has effective solid tumor ablation effect with 808 nm NIR light irradiation, revealing the potential of these nanocomposites as a NIR‐mediated dual‐modal therapeutic platform for cancer treatment. Abstract : An 808‐nm‐light‐mediated, antitumor, synergistic photothermal and photodynamic therapy nanosystem based on tungsten oxide@indocyanine green (WO@ICG) nanocomposites has been successfully constructed. These WO@ICG nanocomposites exhibit fascinating in vitro and in vivo dual‐modal phototherapeutic properties under single 808 nm light irradiation, including therapeutic potential in cultured HeLa cells and HeLa tumor‐bearing mice.